Mechanical behavior of ferroelastic porous La0.6Sr0.4Co0.2Fe0.8O3−δ prepared with different pore formers. Issue 17 (1st December 2017) - Islam, M.N.; Araki, W.; Arai, Y.
Abstract: The present work investigated the mechanical behavior of porous La0.6 Sr0.4 Co0.2 Fe0.8 O3− δ LSCF under uniaxial compression. The porous (LSCF) samples with the same grain size but different porous structures with 1.5–41% of porosity were prepared using three different pore formers. All the samples had ferroelastic domains and exhibited ferroelastic mechanical behaviors under uniaxial compression. Initial and loading moduli as well as critical stress monotonically decreased and remnant strain increased with increasing the porosity. The initial modulus can be determined by the actual porosity regardless of porous structure or grain size, whereas the other properties were more sensitive to experimental condition such as loading rate and maximum applied stress. Compressive fracture strength could be significantly influenced by porous structure.